Mass Graves and Imagined Identities in Zimbabwe. Issue 4 (2nd October 2018) - Chikonzo, Kelvin; Muwonwa, Ngonidzashe
ABSTRACT: This article analyses the construction of imagined identities of Zimbabwean nationhood in two televised documentaries, Nyadzonia Massacre and Colonial Era Atrocities, aired on Zimbabwe national television. Using qualitative semiotic analysis and borrowing from post nationalism, this article analyses how the two documentaries interweave memory and violence with the politics of nationhood and belonging during the Third Chimurenga in Zimbabwe. The paper also analyses how the films were packaged in order to undermine the semiotic resistance and autonomy of the viewer to create oppositional readership of the films.